2020
DOI: 10.1038/s41436-020-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ancestry analysis on >93,000 individuals undergoing expanded carrier screening reveals limitations of ethnicity-based medical guidelines

Abstract: Purpose: Carrier status associates strongly with genetic ancestry, yet current carrier screening guidelines recommend testing for a limited set of conditions based on a patient's self-reported ethnicity. Ethnicity, which can reflect both genetic ancestry and cultural factors (e.g., religion), may be imperfectly known or communicated by patients. We sought to quantitatively assess the efficacy and equity with which ethnicity-based carrier screening captures recessive disease risk. Methods: For 93,419 individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Evaluation of genetic syndromes in diverse populations is essential for syndrome recognition and diagnosis (Koretzky et al, 2016; Kruszka et al, 2019). A limitation of our study is individuals self‐reported ancestry (Kaseniit et al, 2020). Genetically defined ancestry would have been more accurate, but was outside the scope of this investigation (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of genetic syndromes in diverse populations is essential for syndrome recognition and diagnosis (Koretzky et al, 2016; Kruszka et al, 2019). A limitation of our study is individuals self‐reported ancestry (Kaseniit et al, 2020). Genetically defined ancestry would have been more accurate, but was outside the scope of this investigation (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, those who self-identify with a specific race/ ethnicity may be at odds with ancestry defined genetically, which is of relevance to carrier screening. 11,12 A recent report demonstrated that relying on self-identification of AJ ancestry as a criteria to screen for conditions common in the AJ population is imperfect. 13 It is important that carrier screening goes beyond commonly recognized at-risk groups and includes diverse populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a panel that detects the 23 most common CFTR pathogenic variants fails to identify nearly three-quarters of affected pregnancies in Hispanic persons compared to full sequencing of the gene with deletion and duplication analysis (8). Similarly, reduced costs of sequencing have allowed for much broader lists of genes that can be screened, no longer limiting the identification of at-risk couples to only those of certain ethnicities for small sets of conditions historically thought-often incorrectly-to be most prevalent in those ethnicities (9,10). At present, ACOG recognizes both ethnicity-based screening and expanded carrier screening (offered without regard ethnicity) as acceptable options for carrier screening.…”
Section: Impact Of Wgs On Fetal Screeningmentioning
confidence: 99%